Pre-vaccination IgG screening for mumps is the most cost-effectiveness immunization strategy among Health Care Workers - Luca Coppeta; Ottavia Balbi; Savino Baldi; Antonio Pietroiusti; Andrea Magrini (Taylor & Francis Group, 2019)
Health Care Workers (HCWs) have an increased risk of contracting contagious disease, including mumps. In January 2017 the Italian National Vaccine Prevention Plan 2017-2019, recommended the administration of a dose of MMR vaccine (Measles-Mumps-Rubella) to the Health Care Workers (HCWs) that, working in a risky environment, did not carry out the complete vaccination cycle of MMR or that are seronegative for at least one of the three vaccine viruses. In October of the same year, the Advisory Committee on Immunization Practices (ACIP) recommended a third dose of a vaccine containing Mumps Virus for people previously vaccinated with 2 doses, belonging to a group or to a population at increased risk of acquire mumps in the event of an epidemic. We analyzed the clinical records and values of mumps-specific IgG antibodies of 3032 HCWs (mean age 32.80 ± 10.75 years), that underwent occupational health surveillance between January 1st 2017 and March 31th 2018. The HCWs were also screened for measles, rubella, mumps using serological methods. 13% (405) was seronegative for mumps, especially among HCWs between 18 and 36 years. We calculated the cost-effectiveness of two-doses and three-doses MMR vaccination. The cost of vaccination without screening was significantly more expensive (cost difference: 99 712 € and 184 996 €) both in case of two-dose and three-dose MMR vaccination respectively. Our study suggests that, in HCWs, the assessment of the mumps antibody titer before vaccination may be a useful complement to vaccination itself, because it is more accurate and cost-effective than direct immunization of unvaccinated subjects.